Peningkatan Literasi Artificial Intelligence Melalui Sosialisasi Peluang Bisnis Digital Bagi Mahasiswa - Nurul Ittaqullah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Artificial Intelligence (AI) has become one of the most transformative technologies in the digital era and significantly influences business development, entrepreneurship, and workforce transformation. However, many university students still have limited understanding regarding the practical implementation of AI in digital business opportunities. This community service activity aimed to improve students’ literacy and awareness regarding the utilization of Artificial Intelligence for digital entrepreneurship development. The activity was conducted through socialization sessions, interactive discussions, demonstrations of AI-based digital tools, and practical case studies related to online business opportunities. Participants consisted of undergraduate students from the Faculty of Economics and Business. The implementation method included preparation, material delivery, simple simulation, and evaluation stages. The results indicated an increase in participants’ understanding of AI concepts, digital business opportunities, content creation strategies, and the ethical use of AI technology. Participants also demonstrated higher motivation to develop digital entrepreneurship initiatives utilizing AI-based platforms such as content generators, chatbot services, and digital marketing tools. This activity contributes to strengthening students’ digital competencies and entrepreneurial mindset in facing the challenges of the digital economy era. Furthermore, the program is expected to encourage universities to continuously integrate AI literacy into academic and community empowerment activities.